2020
DOI: 10.3389/fmicb.2020.591945
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Riboflavin-Overproducing Lactiplantibacillus plantarum Strains to Survive Under Gastrointestinal Conditions

Abstract: Riboflavin, vitamin B2, is essential for humans and has to be obtained from the diet. Some lactic acid bacteria (LAB) produce this vitamin, and they can be used for in-situ fortification of foods. This could be an alternative to supplementation with chemically synthesized vitamin, to palliate riboflavin deficiencies in specific groups of people. Moreover, if the producing LAB could survive in the gastrointestinal stress (GIT) they could be added as probiotics in this environment. In the present study we tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Besides riboflavin production and fermentation capacity, it is important to consider the gastrointestinal adaptation properties of lactobacilli to efficiently implement them for real-life food biofortification or as beneficial supplements ( 16 , 21 ). Here, we showed that L. reuteri AMBV339 survives in simulated gastric juice, suggesting that it is resistant to the harsh conditions of the stomach before, during and after a meal, and can be transported live to the small intestine where riboflavin is absorbed, as we demonstrated via passive transport in the gastrointestinal dialysis model (GIDM-colon) and active transport via human intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides riboflavin production and fermentation capacity, it is important to consider the gastrointestinal adaptation properties of lactobacilli to efficiently implement them for real-life food biofortification or as beneficial supplements ( 16 , 21 ). Here, we showed that L. reuteri AMBV339 survives in simulated gastric juice, suggesting that it is resistant to the harsh conditions of the stomach before, during and after a meal, and can be transported live to the small intestine where riboflavin is absorbed, as we demonstrated via passive transport in the gastrointestinal dialysis model (GIDM-colon) and active transport via human intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the acidification capacity of these bacteria can inhibit pathogenic growth, typically resulting in longer shelf life ( 20 ). In addition to the ability of the lactobacilli to produce riboflavin in a range of food matrices, it can be beneficial if the selected strains survive the gastrointestinal tract, so that the vitamins can be produced in situ at the target site to further enhance delivery and maximize the chance of reaching required daily intake levels ( 16 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, bacterium–fungus combinations were tested in liquid medium: GPP (Glucose-Proline-Phosphate) minimal medium [ 21 ], Czapek’s Dox [ 29 ], CDM (chemical defined medium) [ 30 ] and plantarum minimal medium (PMM5) [ 27 ], all with glucose as a carbon source. In subsequent experiments, we used MRS broth (Condalab) with glucose as a control medium and MRS broth without dextrose and beef extract (Condalab) with 1% ( w / v ) starch as the carbon source.…”
Section: Methodsmentioning
confidence: 99%